Molecular docking studies of various bioactive molecules from Withania somnifera against bronchial asthma - Ali, Nafaa H.; Sheikh, Khursheed A.; Naqvi, Maaz; Rehman, Sana; Gulati, Kavita; Ray, Arunabha (Current Issues in Pharmacy and Medical Sciences, 2026)
Asthma is a complex respiratory disorder characterized by chronic inflammation and hyperresponsiveness of the bronchial airways. Despite the availability of effective treatments and diagnostic methods, some patients remain symptomatic and exhibit a poor response to conventional asthma therapies. Herbal drugs are considered safe and effective alternative approaches that may target multiple pathogenic pathways involved in asthma. Withania somnifera (WS) is a well-known medicinal plant containing several bioactive compounds and has been extensively studied for its anti-inflammatory and immunomodulatory properties. The present study aimed to explore the potential mechanisms of WS bioactive molecules in the treatment of asthma using an in silico screening approach. Six active phytoconstituents (ligands) of WS were docked against two target receptor proteins, namely the glucocorticoid receptor and the β₂-adrenergic receptor, to predict binding energies and binding patterns. The obtained results were compared with those of known ligands of the glucocorticoid and β₂-adrenergic receptors (fluticasone and salbutamol, respectively). Among all docked ligands, withaferin A, withanolide D, and withanolide B exhibited the highest binding affinities (lowest estimated free binding energy of -8.4 kcal/mol) toward the glucocorticoid receptor (GR). In contrast, the WS alkaloids tropine and anaferine showed lower affinities, as evidenced by higher binding energy values. Furthermore, withanolide D and withanolide B demonstrated the highest affinity for the β₂-adrenergic receptor among the screened compounds, whereas salbutamol and the plant alkaloids tropine and anaferine exhibited lower affinity toward the β₂-adrenergic receptor compared with the plant withanolides. WS bioactive compounds, particularly withanolides, are predicted to possess multitarget anti-inflammatory and bronchodilator potential. Further experimental validation is warranted.